2011
DOI: 10.4028/www.scientific.net/kem.493-494.566
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Bioglass<sup>®</sup>-Titania Reinforced Hydroxylapatite Composite

Abstract: Hydroxylapatite, titania and Bioglass 45S5 are the components generally used for the production of bioactive biomaterials for years. In literature, although the binary composites with the permutation of three components exist, a ternary composite has not yet been tried. Primarily, Bioglass 45S5 was cast, its thermal analysis (Differential thermal analysis (DTA), dilatometric analysis), phase analysis (X-Ray Diffraction (XRD) ), microstructural characterization (Scanning Electron Microscopy (SEM) ) were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Ca, P, Mg, Na, O, and Zr were observed in the EDS analyses (see Figure 7), and it is known that these elements are included in the human body by showing low toxicity and having an effect on mechanical properties, bioactivity and biocompatibility. 1113 The concentration of Ca and P ions (CN2) increased with the increase in the waiting time in the SBF. Pores and fissures are the first locations to become saturated with released Ca and P ions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ca, P, Mg, Na, O, and Zr were observed in the EDS analyses (see Figure 7), and it is known that these elements are included in the human body by showing low toxicity and having an effect on mechanical properties, bioactivity and biocompatibility. 1113 The concentration of Ca and P ions (CN2) increased with the increase in the waiting time in the SBF. Pores and fissures are the first locations to become saturated with released Ca and P ions.…”
Section: Resultsmentioning
confidence: 99%
“…In studies, 913 bio-glass reinforced HA composites have been investigated because of their chemical composition including components such as SiO 2 , CaO, P 2 O 5 , Na 2 O, and MgO. The reason for using bio-glass in these studies was that the components present in the chemical structure of bio-glasses have biocompatible and non-toxic properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This prompted us to create new composite biomaterials combining the properties of both bioactive glasses and titania. Cetiner et al recently reported the production and characterization of new, three‐component composites made of hydroxylapatite, titania, and Bioglass 45S5 . Beherei et al obtained biocomposites made of Bioglass 45S5 and titania that showed high bioactivity and compressive strength comparable to cortical bone …”
Section: Introductionmentioning
confidence: 99%
“…Cetiner et al recently reported the production and characterization of new, threecomponent composites made of hydroxylapatite, titania, and Bioglass 45S5. 21 Beherei et al obtained biocomposites made of Bioglass 45S5 and titania that showed high bioactivity and compressive strength comparable to cortical bone. 22 We have examined the hypothesis that the introduction of gel-derived bioactive glass component to the TiO 2 base will result in innovative biocomposites suitable for medical applications.…”
Section: Introductionmentioning
confidence: 99%